MORAL PHILOSOPHY OF CAPITALISM IN VIEW OF THE TRADING ETHOS OF JAVANESE ISLAMIC PEOPLE - Daryono Daryono; Dwi Widi Pratito Sri Nugroho (Jurnal Ekonomi, 2022)
The results of this article are based on library research aimed at understanding capitalism in the light of the Javanese Muslim trading ethos. His understanding refers to the opinion of experts that the discrepancy between the capitalist economy and the trading ethos of Javanese Muslims lies in the objectification of Islam as a world view and cultural life in post-colonial conditions. The method of analysis through socio-historical and normative, normative ethics as well as meta-ethics can understand the theoretical construction of the Javanese Muslim trade ethos as the objectification of Islam through three ways of being kind, namely, being kind or respectful and caring about anything, being kind or respectful and getting along and caring for anyone and, according to the culture or religious experience of Javanese Muslims in that condition. These three ways of being kind were practiced during Mangkunegara IV. On the one hand, the practice of his trade ethic is different from the morals of capitalism. However, on the other hand, being able to achieve humane progress, especially in the field of trade, the Mangkunegaran kingdom was always called Kala Sumbaga (as a prosperous era). Because of that, this theoretical construction might be an alternative way of thinking with an ethical vision at the regional or national level.